(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article offers a theoretical and practical analysis of aspects of the methodology for evaluating the results of cognitive and econometric modeling of socio-economic development of regions on the example of the Republic of Uzbekistan.